A miséria da teologia: um estudo sobre práticas e praticantes da religiosidade pentecostal - Lopes, Rodrigo Barbosa (2016)
This thesis is the result of a study that sought to understand and discuss how and why men and women, mostly workers, commit to a religiosity, recognized as Pentecostal. It is understood that arrangements are established expression and protest of a historical time, serving as an important way to understand the social fabric built in recent decades by different social subjects. The text is organized into four chapters and as a main argument, seeks to recognize how religiosity served/serves as a culpability space, mingled with the social and cultural conditions of the time. Going forward, it is an environment also claim that, aware of their conditions, men and women seek to deny the world in which they live and overcome it at any cost from the social and cultural conditions of each. The unfolding of this condition are other aspects of the pentecostal developed in the country in the last four decades. Unlike other religiousness, Pentecostal churches have turned to proselytizing practices with massive use of media and theater actions means. By extending the look, it is perceived as behind the scenes of the churches of prosperity, such as the Universal Church of the Kingdom of God, International Grace World, among others, political disputes are noticeable between ministers and workers who galgam conditions and social situations by through the office of faith. Although many are chosen few attain some material prosperity. The last aspect investigated and questioned here are the political relations established in the kingdom behind the scenes, and has, as its objective, think how men and women can understand the arrangements established between party politics and the doctrine of prosperity Pentecostalism. When you cut the last decade, it is noted as the Brazilian political scene was associated with the Pentecostal environment, and in this study, seek to understand and discuss how men and women fit into this social fabric. This thesis has the purpose to criticize / combat religions, but develop a critical and political look at the cold, raw and heartless world, able to serve as a vector to express religiousness that such a historical moment. What remains, as a defense, is to share the aspiration of utopias that can be real, possible and concrete.